Modified dispersive liquid-liquid microextraction using green solvent for determination of polycyclic aromatic hydrocarbons (PAHs) in vegetable samples [Pengekstrakan mikro cecair-cecair serakan yang terubahsuai dengan pelarut hijau untuk penentuan polisiklik aromatik hidrokarbon (PAHs) dalam sampel sayur Sayuran] - Kin C.M.; Chander P.D.; Shing W.L. (Malaysian Society of Analytical Sciences, 2023)
According to International Agency for Research on Cancer (IARC), most of Polycyclic Aromatic Hydrocarbons (PAHs) known as genotoxic human carcinogen and mutagenic. PAHs represent as poorly degradable pollutants that exist in soils, sediments, surface water and atmosphere. A simple, rapid and sensitive extraction method termed modified Dispersive Liquid-Liquid Microextraction (DLLME) using green solvent was developed to determine PAHs in vegetable samples namely radish, cabbage and cucumber prior to Gas Chromatography Flame Ionization Detection (GCFID). The extraction method is based on replacing chlorinated organic extraction solvent in the conventional DLLME with low toxic solvent, 1-bromo-3-methylbutane without using dispersive solvent. Several experimental factors such as type and volume of extraction solvents, extraction time, confirmation of 12 PAHs by GC-MS, recovery percentages on vegetable samples and the comparative analysis with conventional DLLME were carried out. Both DLLME were successfully extracted 12 types of PAHs. In modified DLLME, the recoveries of the analytes obtained were in a range of 72.72 88.07 % with RSD value below 7.5 % which is comparable to the conventional DLLME. The use of microliter of low toxic extraction solvent without addition of dispersive solvent caused the method is economic and environmental friendly which is fulfill the current requirement, green chemistry based analytical method. 2016, Malaysian Society of Analytical Sciences. All rights reserved.